PENGARUH FAKTOR SOSIAL EKONOMI PETERNAK TERHADAP POLA PENGELOLAAN SAPI PERAH DI KECAMATAN LEMBANG, KABUPATEN BANDUNG BARAT - Ruth Roselin Nainggolan (Jurnal Ilmiah Wahana Bhakti Praja, 2017)
ABSTRACT West Java provincial animal husbandry department reported that since 2012 s / d 2015 milk production in West Java has decreased on average by 4.58%. This is due to breeding patterns are not optimal and the reduced population of dairy cows.The business scale dairy farmers in Lembang district mostly small ie 2-3 individuals per household. This study aims to determine how much influence population characteristics (age, education and experience breeding) on the pattern of a dairy farm in Lembang district. Residents were used as the respondents in the study of 90 people who have dairy cattle business. Sampling was done by cluster method is simple and random gradually perfect. Statistic data analysis used was chi square test to see how the social economic correlate with the scale and financial management. The entire calculation of statistical tests using SPSS (Statistical Program For Service and Solution) version 17.0. Based on the research results of research that the business scale dairy cattle in Lembang district, Bandung regency is 2-4 tails, due to the capital factor and price competition so that farmers only assume the dairy farm as a sideline; social economic factors were correlated with the scale and pattern of financial management of dairy cattle Lembang district, West Bandung regency significantly are education, whereas age and breeding experience did not correlate significantly.